Analysis of Search Engine Optimization Application on Markas Gamers' Website - Permatasari, Angelina; Pangestu Wonohardjo, Eduard; Hidayat, Desman; Hendrawaty, Manise; Hartato, Hartato (Journal of Multidisciplinary Issues, 2022)
Objective – Along with the rapid development of information technology and the increasing number of websites, search engines like Google will be increasingly strict in sorting out the best websites that have useful information for their users. This causes website owners to increasingly aggressively improve the quality and popularity of their websites in various ways, such as using advertisements, branding on social media, to the use of SEO (Search Engine Optimization) to support the quality of the website so that it can compete in search engine ranking results. Methodology – Method used in this research is by redesigning the user interface and applying SEO methods. Findings – Being able to improve the metrics of the website can be significantly improved both from its UR and DR and increase visitor traffic as a source of profit for a website. Novelty – This research was conducted on a new website that initially had not implemented SEO and had not been maximized in designing its User Interface. Keywords: Google; Markas Gamers; Redesign; SEO; Website Optimization